The Differences of Counseling Satisfaction Between Counselees With Counseling Style Matches With Their Personalities and Those Who Are Not - Lucia Hernawati; Bagus Wismanto; Rachmad Djati Winarno (Universitas Katolik Soegijapranata, 2018)
This study aimed to determine the differences in counseling satisfaction between counselees who get counseling services in accordance with the characteristics of his personality and get appropriate counseling style and those who do not. The hypothesis proposed in this study was that there was the influence of counselee personality characteristics, counseling style that was in accordance with the satisfaction of counseling.Two hundred and fifty-three men and women who have lived in Semarang for at least 1 year, aged between 18 and 55 years and came from various professions participated in this research. The recruitment of participants was voluntary to participants who were students whereas for non-student participants, there is assignment from the working institutions. The experimental research method was applied by grouping the subjects in the experimental and control groups randomly. A counseling style that matches the characteristics of the participants' personality was given in the experimental group, whereas in the control group it was not. Further comparison of the experimental and control groups was conducted to prove the differences in counseling satisfaction of both groups. Two instruments used in this study were: (1) the Indonesian version of the NEO Personality Inventory-Revised (NEO-PI-R) developed by Costa & McCrae (2) Client Satisfaction Questionnaire (CSQ-8). It was found that in general all participants were satisfied with the counseling service received. T-test analysis was found that there was no difference in counseling satisfaction between experimental and control groups